2010
DOI: 10.1097/eja.0b013e32833679e3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of laryngeal mask airway Supreme versus laryngeal mask airway ProSeal: a randomized controlled trial

Abstract: The LMA Supreme has lower oropharyngeal leak pressures than the LMA ProSeal. The success of the first attempt insertion was higher for the LMA Supreme. The LMA Supreme is a safe, efficacious and easy-to-use disposable supraglottic airway device in elective ambulatory procedures. The higher rate of success on first attempt insertion may make it more suitable as an airway rescue device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 18 publications
7
89
3
4
Order By: Relevance
“…(8) Other studies also demonstrated that the Supreme was better in terms of first attempt success rates. (20,21) The difference in the findings could be attributed to the SAD insertion techniques we used as compared with the other studies, e.g. Van Zundert et al employed the laryngoscope-and gastric tube-guided SAD insertion techniques in their study.…”
Section: Discussioncontrasting
confidence: 43%
“…(8) Other studies also demonstrated that the Supreme was better in terms of first attempt success rates. (20,21) The difference in the findings could be attributed to the SAD insertion techniques we used as compared with the other studies, e.g. Van Zundert et al employed the laryngoscope-and gastric tube-guided SAD insertion techniques in their study.…”
Section: Discussioncontrasting
confidence: 43%
“…In clinical trials, the SLMA has been found comparable with the reusable LMA ProSeal TM (PLMA), 1 with the SLMA having a higher rate of success on first attempt insertion. [2][3][4][5] Previous studies have shown the use of the PLMA and SLMA in non-paralyzed patients, 6 in anesthetized patients with a simulated difficult airway, 7 and in patients undergoing laparoscopy procedures. 8,9 More recent studies and case reports have shown that it is effective in providing ventilation and oxygenation in challenging cases, such as the morbidly obese patients, 10 patients in the prone position, 11,12 and those who have suffered from multiple trauma.…”
Section: Résumémentioning
confidence: 99%
“…Six of the studies compared the LMA Supreme with the LMA Proseal. 10,[13][14][15][16][17] The remaining studies compared the LMA Supreme with the LMA Classic, 23 i-gel, [18][19][20] facemask, 21 or endotracheal tube. 22 In the six RCTs comparing the LMA Supreme with the LMA Proseal, 418 patients were identified and 295 (70%) of those were female.…”
Section: Use Of Lma Supreme In Normal Airway/elective Surgerymentioning
confidence: 99%